EFEKTIVITAS PENGGUNAAN MEDIA KOMIK DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DI PONOROGO - Nuraini dan Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2017)
Comic media is one form of media and learning resources that can help students and can replace the teacher position in learning activities both in class and outside the classroom. Comic media can be used in a two-way learning process, namely as a learning tool and as a medium of learning that can be used alone by students. From field observation that the learning of PAI in the form of learning comic has never been utilized. So that the presence of learning media in the form of comics is expected to help teachers or lecturers in the process of learning in the classroom to run in an effective and efficient quality. Comic media can be applied to convey messages in various sciences, and because of its attractive appearance. This media is very interesting in students' lives and is widely available in reading stores as well as the fact that some of the students recognize and memorize the characters of the comics they see.This research will be conducted on junior high school 6 Grade 7 or 8 students, because at that time it is a transition period to adult so it needs a media to improve learning achievement, quality and efficiency of learning. This study aims to produce or develop a product and test it, namely improving the quality and efficiency of learning Islamic religious education through the use of comics as a medium of learning. The new product is PAI comic learning media. This research type is Quantitative Research that is by conducting experiment of using a comic learning media product in PAI splitting by using Gain Score Test. Based on the results of the Gain Score Test in the control class obtained an average value of 0.3 and the treatment class obtained an average value of 0.57. So it can be concluded that treatment classes that use PAI comic media have significantly improved learning outcomes compared to control classes using conventional learning media.